TINJAUAN BENTUK KARYA SOLO PIANO “THE DANCER” CIPTAAN LEVI GUNARDI - Haryandri, R.A. Endlessia (Jurnal Penelitian Musik, 2020)
Abstract: The work of "The Dancer" very popular because of its uniqueness, namely solo piano works with thick nuances of traditional Balinese music. This work is the creation of composers from Indonesia that are rarely interested in researching, while this work is a unique work because there is a blend of nuances of Balinese music and pop music played on piano instruments. The research method used was descriptive qualitative research. The object under study was the score of Levi Gunardi's solo piano "The Dancer". Data analysis was performed by processing data relating to research. Stages in conducting data analysis include: (1) looking at source books about the history of music as well as source books about the form of music. (2) examines each of the smallest parts of Levi Gunardi's song "The Dancer". (3) reviewing the form of the song "The Dancer" by Levi Gunardi. the results of the study stated that Levi Gunardi's solo piano "The Dancer" consists of 153 bars using Balinese pelaton pentatonic scales namely Dang, Ding, Dung, Dong, Deng in B major tonality and has a 2-part song form which is divided into AB-A '-B'. The chord progressions contained in this work use chord progressions in the diatonic scale, while the melody remains consistent using the pentatonic pelog scale in B Major tonality, the tempo is slow but is played lightly and expressively. Piano playing techniques used include arpeggios, block chords, fingering